DCE-MRI quantitative transport mapping for noninvasively detecting hypoxia inducible factor-1α, epidermal growth factor receptor overexpression, and Ki-67 in nasopharyngeal carcinoma patients. (November 2021) - Huang, Weiyuan; Zhang, Qihao; Wu, Gang; Chen, Pian Pian; Li, Jiao; McCabe Gillen, Kelly; Spincemaille, Pascal; Chiang, Gloria C.; Gupta, Ajay; Wang, Yi; Chen, Feng
Highlights: Our study is the first to report the correlation between DCE-MRI parameters and HIF-1α, EGFR, and Ki-67 expression levels, using both QTM and traditional models in NPCs. DCE-MRI using the QTM model may be a noninvasive biomarker to differentiate between high and low expression of HIF-1a, EGFR, and Ki-67 in NPCs. | u | was the best classifier for discriminating between the high-expression and low-expression subgroups of HIF-1a and Ki-67.K trans was the best classifier for discriminating between the high-expression and low-expression subgroups of EGFR. Abstract: Background: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has the potential to noninvasively detect expression of hypoxia inducible factor-1-alpha (HIF-1α), epidermal growth factor receptor (EGFR), and Ki-67 in nasopharyngeal carcinoma (NPC) by quantitatively measuring tumor blood flow, vascularity, and permeability. Purpose: We aim to explore the utility of DCE-MRI in detecting HIF-1α, EGFR, and Ki-67 expression levels using traditional Kety's/Tofts' modeling and quantitative transport mapping (QTM). Materials and methods: Eighty-nine NPC patients underwent DCE-MRI before treatment were enrolled. DCE-MRI was processed to generate the following kinetic parameters: | u | and D from the QTM model, tumor blood flow (TBF) from Kety's model, and K trans, V e, and K ep from Tofts' model. Pretreatment levels of HIF-1α, EGFR, and Ki-67 were assessed by immunohistochemistry and classified into low and high expression groups. Results: | u | ( p  < 0.001) and TBF ( p  = 0.015) values were significantly higher in the HIF-1α high-expression group compared to low-expression group. Only K trans ( p  = 0.016) was significantly higher in the EGFR high-expression group. Only | u | ( p  < 0.001) values were significantly higher in the Ki-67 high-expression group compared to low-expression group. Multiple linear regression analyses showed that | u | independently correlated with HIF-1α and Ki-67 expression, and K trans independently correlated with EGFR. The areas under the ROC curves of | u | for HIF-1α and Ki-67, and K trans for EGFR were 0.83, 0.74, and 0.70, respectively. Conclusion: | u | and K trans derived from DCE-MRI may be considered as noninvasive imaging markers for detecting hypoxia and proliferation in NPC patients.